The strategic management and its relationship with organizational success: Empirical study on the pharmaceutical industry sector in Jordan - Alsarireh, Dalal Aqil (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims to test and evaluate the relationship between strategic renewal and organizational success of the pharmaceutical industry sector companies in Jordan. The descriptive and analytical approach was used. and the study population consists of (1000) leaders and managers in the top and middle management level in the pharmaceutical industries sector companies in Jordan. And a random sample was chosen of (420) participants. In order to reach the objectives of the study, a questionnaire was developed to collect data. The study concluded that the independent variable, which is strategic renewal, is available in the companies at a high level. Where the exploration of opportunities came in the first rank, which corresponds to a great degree of appreciation with a mean (4.03).Then came the coordinated strategic action, strategic imagination, the exploitation of opportunities, and the genesis of new ideas, ranked respectively in terms of relative importance. It was found that the researched companies achieved a high level of organizational success with an overall average of (3.81), in addition to the existence of a statistically significant correlation between strategic renewal and organizational success, and the study recommended maintaining the level of practical application of strategic renewal in the pharmaceutical industry sector companies in Jordan. And that is through practical steps that companies follow and work to develop and sustain the level of organizational success by developing and strengthening the process of strategic renewal in all functional areas of companies.